2004
DOI: 10.1094/asbcj-62-0029
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Primary Fermentation of Beer with Yeast Immobilized on Spent Grains—The Effect of Operational Conditions

Abstract: A one-stage continuous primary beer fermentation with immobilized brewing yeast was studied. The objective of the work was to optimize the operational conditions (aeration and temperature) in terms of volumetric productivity and organoleptic quality of green beer. The system consisted of an internal-loop airlift reactor and a carrier material prepared from spent grains (a brewing by-product). An industrial wort and yeast strain were used. The immobilized biomass (in amounts from two to sevenfold greater than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 18 publications
5
46
1
1
Order By: Relevance
“…A similar trend was observed by Virkajärvi et al 38 during the continuous fermentation of high-gravity and very-highgravity worts ranging from 15 to 24°Plato. The ADF and RDF obtained in the present work for the 13.4°Plato wort also resembled those previously attained with an airlift reactor system using BSG as the carrier 5,6 . Notwithstanding, the RDF (56.8%) obtained for the highest gravity wort was lower than that found for a one-stage tubular bioreactor with yeast immobilised in porous glass beads (65%) 38 .…”
Section: Influence Of Wort Original Gravity (Og) On Fermentative Parasupporting
confidence: 86%
See 1 more Smart Citation
“…A similar trend was observed by Virkajärvi et al 38 during the continuous fermentation of high-gravity and very-highgravity worts ranging from 15 to 24°Plato. The ADF and RDF obtained in the present work for the 13.4°Plato wort also resembled those previously attained with an airlift reactor system using BSG as the carrier 5,6 . Notwithstanding, the RDF (56.8%) obtained for the highest gravity wort was lower than that found for a one-stage tubular bioreactor with yeast immobilised in porous glass beads (65%) 38 .…”
Section: Influence Of Wort Original Gravity (Og) On Fermentative Parasupporting
confidence: 86%
“…Recent studies [4][5][6] have demonstrated the feasibility of continuous primary fermentation of all-malt worts with original gravities below 14°Plato, using brewing yeast immobilised on BSG. In these studies, the ethanol concentration in the produced green beers was lower than 5% (v/v).…”
Section: Influence Of Wort Original Gravity (Og) On Fermentative Paramentioning
confidence: 99%
“…The excess cell growth in continuous fermentation systems is often a result of over-aeration. There have been several studies on the influence of aeration on by-product formation in continuous systems 8,50,111 . Despite this, the results are difficult to transfer between different systems due to a lack of comprehensive engineering data on oxygen transfer rates in various types of bioreactors applied for continuous beer fermentation to date.…”
Section: Vicinal Diketonesmentioning
confidence: 99%
“…The majority of these interventions are based on the stimulation of the growth intensity, e.g. dissolved oxygen concentration and temperature, enhancing the higher alcohol formation 8,49,88 . A positive effect on higher alcohol production has been provoked also by the immobilization-induced acceleration of cell metabolism 82,83 .…”
Section: Higher Alcoholsmentioning
confidence: 99%
“…The cell viability was measured by counting the dead cells stained with methylene blue. Immobilised biomass was determined according to Brányik et al (2004).…”
Section: Microorganismsmentioning
confidence: 99%